The possibilities of predicting the individual risk of cervical cancer in women of reproductive age using mathematical modeling - L. A. Klyukina; E. A. Sosnova; A. A. Ishchenko; M. M. Davydov (Опухоли женской репродуктивной системы)
Background. Cervical cancer (CC) refers to cancer of visual localization and in women of reproductive age remains one of the most common oncological diseases. The carcinogenesis of CC is caused by the persistence of highly oncogenic types of human papillomavirus (HPV), the level of carcinogenicity of which is the highest based on the criteria of the International Agency for Research on Cancer. However, cervical carcinogenesis does not occur in all cases of persistence of highly oncogenic types of HPV. This, in turn, determines the need for a thorough search, study and analysis of possible cofactors that can lead to neoplastic changes in the cervix.Aim. To develop a model for predicting the individual risk of CC in women of reproductive age, taking into account clinical, anamnestic, laboratory and histological data.Materials and methods. The material for the study was retrospective examination data from 251 patients of reproductive age who were treated at the Center for Gynecology and Reproductive Technologies of the National Medical Research Center “Medical and Rehabilitation Center”, Ministry of Health of Russia in the period 2015–2022. Results. Highly oncogenic HPV types were significantly more common in the group of patients with verified СС who took combined oral contraceptives (COC), compared with patients who did not take COC (p = 0.035). Multifactorial analysis allowed us to determine that long-term use of СОС for a total of more than 7 years is associated with a tendency to increase the risk of developing СС (hazard ratio 1.68; 95 % confidence interval 1.1–2.5; p = 0.010). According to the results of statistical calculation, the values of regression coefficients were obtained and the tendency to increase the risk of developing CC was predicted in the presence of such factors as: HPV type 16 persistence, body mass index, and the duration of COC intake in years.Conclusion. Thus, taking into account all possible risk factors for CC, the negative effect of cofactors, namely increased body mass index and prolonged intake of COC, on the course of HPV as the leading etiological factor of breast cancer, will allow us to identify groups at increased risk of developing CC, form an individual algorithm for monitoring and examination throughout the entire period of taking COC, as well as conduct individual cancer prevention by limiting the duration of taking COC.